Declining Chlamydia and Gonorrhea Diagnoses Among Pregnant Women in South Carolina, 2008 to 2018. Issue 3 (21st March 2021) - Lazenby, Gweneth B.; Savage, Ashlyn H.; Horner, Gwynneth; Richmond, Joshua; Peterman, Thomas A.
Abstract : Diagnoses of chlamydia and gonorrhea decreased over time in a population of pregnant women delivering in an urban, academic medical center in the Southeast. Abstract : Background: Reported US cases of chlamydia and gonorrhea have increased since 2000, whereas studies in select populations suggest that the prevalence of these diseases has decreased. We sought to determine if these diagnoses are increasing among pregnant women delivering at our center. Methods: This is a retrospective study of women delivering at least 1 infant >18 weeks of gestation at the Medical University of South Carolina for 11 years (2008–2018). Using the perinatal information system, we collected maternal race, age, insurer, and chlamydia and gonorrhea screening results during the pregnancy of record. Cochran-Armitage trend analyses were performed to evaluate trends in these diagnoses by delivery year for all women and for age/race subgroups. Results: During the study period, there were 24, 807 deliveries. The median age of women was 28 years (interquartile range, 23–32 years). Five percent (5.0%) of women were diagnosed with chlamydia and 1.2% with gonorrhea. The percent of women diagnosed decreased for both chlamydia (9.6%–3.4%) and gonorrhea (2.5%–1.1%; P < 0.001, trend analyses for both). A higher percentage of Black women had chlamydia and gonorrhea, and both diagnoses declined over time: 17.4% to 6.9% ( P < 0.0001) for chlamydia and 5.8% to 2.1% ( P < 0.0001) for gonorrhea. In a subanalysis of race and age, Black women younger than 25 years experienced the most significant decline in chlamydia diagnoses ( P < 0.0001). Conclusions: We observed declining diagnoses of chlamydia and gonorrhea among pregnant women in our center. Although Black women delivering were more likely to have either diagnoses, they experienced a significant decline in both chlamydia and gonorrhea over time.